IKLIM SEKOLAH DAN EFIKASI DIRI DENGAN MOTIVASI KERJA GURU - Fujiaturrahman, Sukron (JURNAL PENDIDIKAN DASAR, 2016)
Abstract : This correlational research was aimed to see the relationship between school’s climate and self-efficacy with teachers’ work motivation. Teachers’ work situation often changes which might affect teachers’ work motivation. Based on the hypotheses, school climate and self-efficacy were assumed to contribute to teachers’ work motivation. This research used survey method, thirty teachers in public elementary school of district 07 were randomly chosen. Questionnaires were developed and had been through expert judgment, they were validated by using Pearson Product Moment calculation and Alpha Cronbach was used to test reliability. The hypotheses were verified with regression analysis through F-test and the regression models were formulated, and correlation coefficient between the variables of school climate and self-efficacy with teachers’ work motivation. The research result showed that correlation between school’s climate and teachers’ work motivation was .886 (α, .05). The relationship between self-efficacy and teachers’ work motivation was .879 (α, .05). It was found that the correlation between school’s climate and self-efficacy with teachers’ work motivation was .900 (α, .05). It can be concluded that school’s climate and self-efficacy contributed to teachers work’s motivation. Considering the previous research findings, the principals and teachers are urged to maintain conducive school’s climate, either physically or non-physically to result comfortable work environment for the teachers and eventually help students to learn in secure school’s environment. Furthermore, the principals need to educate teachers about the importance of self-efficacy, ways to gain and maintain teachers’ self-efficacy.Keywords: School’s climate, self-efficacy, teacher’s work motivationAbstrak : Penelitian ini adalah sebuah penelitian korelasional yang bertujuan untuk menemukan hubungan iklim sekolah dan efikasi diri dengan motivasi kerja guru. Suasana lingkungan kerja yang dirasakan para guru kerap berubah dan hal itu berdampak terhadap motivasi kerja guru. Berdasarkan hipotesis yang telah dirumuskan, iklim sekolah dan efikasi diri diasumsikan berhubungan dengan motivasi kerja guru. Penelitian ini menggunakan metode survey, 30 orang guru di SDN segugus 07 dipilih secara acak. Instrumen berupa kuesioner divalidasi melalui uji kepakaran dan perhitungan Pearson Product Moment dan uji reliabilitas dilakukan dengan menggunakan Alpha Cronbach. Verifikasi hipotesis dilakukan dengan analisis regresi melalui uji F dan menemukan model persamaan regresi, dan koefisien korelasi antara variabel iklim sekolah, efikasi diri dengan motivasi kerja guru. Hasil penelitian menunjukkan bahwa hubungan antara iklim sekolah dengan motivasi kerja guru adalah .886 (α, .05). Hubungan antara efikasi diri dengan motivasi kerja guru adalah .879(α, .05). Ditemukan koefisien korelasi iklim sekolah dan efikasi diri dengan motivasi kerja guru adalah .900 (α, .005). Dapat disimpulkan bahwa iklim sekolah dan efikasi diri berkontribusi dengan motivasi kerja guru. Dengan mempertimbangkan temuan penelitian tersebut, maka diharapkan Kepala sekolah dan guru senantiasa menjaga iklim sekolah agar tetap kondusif, baik dari segi fisik maupun non fisik, sehingga para guru akan merasa nyaman dan tetap bersemangat dalam bekerja dan tentu sekali hal tersebut juga akan berdampak kepada seluruh siswa.Kata Kunci: iklim sekolah, efikasi diri, motivasi kerja guru